Loin Pain Hematuria Syndrome—a case report. Issue 11 (11th November 2021) - Zeb, Ehtisham; O'Connor, Adam; Sabri, Shariq; Muhammad, Karim; Qureshi, Nafees
Abstract: Loin pain hematuria syndrome (LPHS) is a rare idiopathic condition. LPHS can present with both unilateral and bilateral loin pain, microscopic or macroscopic hematuria. It is a diagnosis of exclusion. The management options for this condition include pain management with narcotics or opioids, renal denervation, kidney autotransplantation and neurectomy or nephrectomy. However, these treatment modalities are the last resort.